Characterization of magnetic nanoparticles from Magnetospirillum Gryphiswaldense as potential theranostics tools. (24th November 2015) - Orlando, T.; Mannucci, S.; Fantechi, E.; Conti, G.; Tambalo, S.; Busato, A.; Innocenti, C.; Ghin, L.; Bassi, R.; Arosio, P.; Orsini, F.; Sangregorio, C.; et al.
Abstract : We investigated the theranostic properties of magnetosomes (MNs) extracted from magnetotactic bacteria, promising for nanomedicine applications. Besides a physico‐chemical characterization, their potentiality as mediators for magnetic fluid hyperthermia and contrast agents for magnetic resonance imaging, both in vitro and in vivo, are here singled out. The MNs, constituted by magnetite nanocrystals arranged in chains, show a superparamagnetic behaviour and a clear evidence of Verwey transition, as signature of magnetite presence. The phospholipid membrane provides a good protection against oxidation and the MNs oxidation state is stable over months. Using an alternate magnetic field, the specific absorption rate was measured, resulting among the highest reported in literature. The MRI contrast efficiency was evaluated by means of the acquisition of complete NMRD profiles. The transverse relaxivity resulted as high as the one of a former commercial contrast agent. The MNs were inoculated into an animal model of tumour and their presence was detected by magnetic resonance images two weeks after the injection in the tumour mass. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We investigated the theranostic properties of magnetosomes (MNs) extracted from magnetotactic bacteria, promising for nanomedicine applications. Their potentiality as mediators for magnetic fluid hyperthermia and contrast agents for magnetic resonance imaging, both in vitro and in vivo, are here singled out. These results, together with the ones previously achieved, state how magnetosomes can represent a good platform to develop a multifunctional nanostructured material suitable for theranostics.